A nonequilibrium thermodynamics perspective of thixotropy - Stephanou, Pavlos S.; Georgiou, Georgios G. (My University, 2018)
We propose a new description of elasto-viscoplastic fluids by relating the notion of thixotropy directly to internal viscoelasticity and network structures through a general, thermodynamically consistent approach. By means of non-equilibrium thermodynamics, a thermodynamically admissible elasto-viscoplastic model is derived which introduces self-consistently and effortlessly thixotropic effects and reproduces at both low and high shear rates experimental data usually fitted with empirical constitutive equations, such as the Bingham and Herschel-Bulkley models. The predictions of the new model are in very good agreement with available steady-state shear rheological data for soft colloidal pastes and blood, i.e., systems exhibiting a yield stress, and with time-dependent rheological data for blood, i.e., during a triangular time-dependent change in the shear rate, exhibiting a hysteresis. The proposed approach is expected to provide the means to improve our understanding of thixotropic fluids.
Keywords: Blood; Constitutive equations; Shear deformation; Shear flow; Viscoplasticity; Yield stress